Manganese accumulation in pancreatic beta-cells and its stimulation by glucose. - Rorsman, P; Berggren, P; Hellman, B (1982)
Electrothermal atomic-absorption spectroscopy was employed for measuring manganese in beta-cell-rich pancreatic islets microdissected from ob/ob mice. The islet content of endogenous manganese was 80 mumol/kg dry wt., which is about half as much as found in the exocrine pancreas. The initial uptake was characterized by two components, with approximate Km values of 35 microM and 3.7 microM respectively. After 60 min of incubation with 0.25 mM-Mn2+, the intracellular concentration of manganese corresponded to an almost 25-fold accumulation compared with that of the extracellular medium. When exposed to 20 mM-D-glucose, the islets retained more manganese, owing to suppression of its mobilization. The glucose inhibition of efflux was prompt and reversible, as indicated from direct recordings of manganese in a perifusion medium. D-Glucose was an equally potent inhibitor of efflux in the presence of 15 microM- and 1.28 mM-Ca2+. The inhibitory action disappeared when metabolism was suppressed by adding 0.1 mM-N-ethylmaleimide or by lowering the temperature from 37 degrees C to 2 degrees C. At a concentration of 0.25 mM, Mn2+ abolished the insulin-releasing action of D-glucose, exerting only moderate suppression of its metabolism. The addition of Mn2+ resulted in inhibition of basal insulin release in the presence of 1.28 mM-Ca2+, but not in a Ca2+-deficient medium. The studies indicate that the previously observed phenomenon of glucose inhibition of 45Ca efflux has a counterpart in the suppression of manganese mobilization from the pancreatic islets. With the demonstration of a pronounced glucose inhibition of manganese efflux, it is evident that Mn2+ may represent a useful tool for exploring the mechanism of glucose-induced retention of calcium in the pancreatic beta-cells.